Nanometer sulfurized polyacrylonitrile positive electrode material and preparation method and application thereof

By preparing nano-sulfurized polyacrylonitrile positive electrode material, the insulator properties and volume expansion effects of elemental sulfur materials in lithium/sodium sulfur batteries are solved, the rate performance and cycle life are improved, and high specific capacity and fast charging and discharge are achieved.

CN119320472APending Publication Date: 2025-01-17SOUTHWEST UNIV
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202411453007.9
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-10-17
Publication Date
2025-01-17

AI Technical Summary

Technical Problem

The elemental sulfur materials in existing lithium/sodium sulfur batteries have problems such as insulator properties, volume expansion effects, and incompatibility with commercial ester electrolytes, resulting in poor rate performance and cycle life.

Method used

Using nano-vulcanized polyacrylonitrile positive electrode material, nanoparticles are formed by mixing acrylonitrile with a specific initiator and calcining and vulcanizing under an inert atmosphere to obtain nano-vulcanized polyacrylonitrile with a particle size of about 100 nm, which improves the degree of vulcanization of the material and Ion diffusion rate.

Benefits of technology

It achieves high specific capacity, long cycle life and fast charging and discharge rate performance, significantly improving the battery performance of lithium-sulfur batteries or sodium-sulfur batteries.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119320472A_ABST
    Figure CN119320472A_ABST
Patent Text Reader

Abstract

The invention relates to a nano sulfurized polyacrylonitrile positive electrode material and a preparation method and application thereof. The preparation method comprises the following steps: acrylonitrile, an initiator and a solvent are mixed and heated for a reaction, the initiator is one or more of azodiisobutyronitrile, azobisisoheptonitrile and dimethyl azobisisobutyrate, and nano polyacrylonitrile particles are obtained; and mixing the nano polyacrylonitrile particles with sulfur, and calcining in an inert atmosphere to obtain the nano vulcanized polyacrylonitrile positive electrode material. Nanoscale polyacrylonitrile particles with the particle size of about 100 nm can be obtained, the nanometer polyacrylonitrile particles have the ultra-short ion diffusion distance, the material is easier to vulcanize, and the obtained nanometer vulcanized polyacrylonitrile is high in vulcanization degree and short in ion diffusion rate and has high specific capacity, long cycle life and rapid charge-discharge rate performance.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the technical field of lithium / sodium-sulfur secondary batteries and relates to a nano-sulfurized polyacrylonitrile positive electrode material and a preparation method thereof and application thereof in lithium-sulfur batteries or sodium-sulfur batteries. Background Art

[0002] The energy density and cost of lithium-ion batteries have reached their development limits, and the development of "post-lithium-ion batteries" with higher energy density and relatively low prices is imminent. Lithium / sodium-sulfur batteries are expected to become the next generation of high-energy-density batteries because of their extremely high theoretical energy density (taking lithium-sulfur batteries as an example, their energy density is as high as 2600Wh / kg). However, the battery also faces many challenges. For example, elemental sulfur and its discharge products are both insulating materials, and sulfur has a large volume expansion effect during the charge and discharge process (the volume expansion rate exceeds 80%); elemental sulfur is incompatible with commercial ester electrolytes and can only work in ether electrolytes. When it works in ether solutions, it will undergo multi-step conversion reactions. The intermediate product polysulfide produced during its charge and discharge process can dissolve in the electrolyte and shuttle back and forth between the positive and negative electrodes, causing a series of problems such as battery self-discharge and metal negative electrode corrosion.

[0003] Compared with the traditional elemental sulfur positive electrode, polyacrylonitrile sulfide is a semiconductor material made of small molecular sulfur fixed on the polymer skeleton through chemical bonding. It is highly compatible with the currently commercialized ester electrolytes, and a single-step solid-solid conversion reaction occurs during the charge and discharge process. There is no phenomenon of polysulfide dissolving in the electrolyte, which fundamentally solves the adverse shuttle effect of the lithium / sodium-sulfur battery system. The above advantages make polyacrylonitrile sulfide have great potential in the process of commercialization. However, all commercial polyacrylonitrile sulfide currently has large particle size (average particle size > 20 microns), which makes it difficult to fully sulfide the deep internal area of ​​the material; the ion solid phase diffusion depth is large and the polymer main chain conductivity is average, resulting in poor rate performance of existing polyacrylonitrile sulfide positive electrode materials.

[0004] Therefore, it is of great research significance and application value to develop a sulfurized polyacrylonitrile positive electrode material using advanced material preparation technology with more complete sulfurization (i.e., sulfur content higher than 50%, higher specific capacity), fast reaction kinetics, excellent cycle stability and rate performance. Summary of the invention

[0005] In view of this, the purpose of the present invention is to develop a nano-sulfurized polyacrylonitrile positive electrode material and a preparation method thereof and an application in a lithium-sulfur battery or a sodium-sulfur battery, so as to obtain nano-scale polyacrylonitrile particles with an ultra-short ion diffusion distance and the material is easier to vulcanize, thereby improving the positive electrode rate, cycle life and charge and discharge specific capacity performance of the sulfurized polyacrylonitrile.

[0006] The technical solution provided by the present invention is as follows:

[0007] A method for preparing a nano-sulfurized polyacrylonitrile positive electrode material comprises the following steps:

[0008] (1) mixing acrylonitrile, an initiator and a solvent and heating them for reaction, wherein the initiator is one or more of azobisisobutyronitrile, azobisisoheptanenitrile and dimethyl azobisisobutyrate, to obtain nano-polyacrylonitrile particles;

[0009] (2) Mixing the nano-polyacrylonitrile particles obtained in step (1) with sulfur, and calcining the mixture under an inert atmosphere to obtain a nano-sulfurized polyacrylonitrile positive electrode material.

[0010] As a preferred technical solution, the particle size of the nano-polyacrylonitrile particles obtained in step (1) is 100±20 nm.

[0011] As a preferred technical solution, in step (1), the solvent is one or more of dimethyl sulfoxide, dimethylformamide, methanol, ethanol, acetone, and water.

[0012] As a preferred technical solution, in the step (1), the amount of initiator corresponding to 1 mL of acrylonitrile is 0.01 to 100 mg.

[0013] As a preferred technical solution, in step (1), the amount of initiator corresponding to 1 mL of acrylonitrile is 0.1 mg.

[0014] As a preferred technical solution, in step (1), the reaction temperature is 30 to 100° C. and the reaction time is 1 to 12 hours.

[0015] As a preferred technical solution, in the step (2), the mixing ratio of the nano-polyacrylonitrile particles and sulfur is 1:1 to 10 by mass.

[0016] As a preferred technical solution, in the step (2), the heating rate is 2 to 10°C / min, the calcination temperature is 100 to 500°C, and the calcination time is 1 to 20 hours.

[0017] As a preferred technical solution, the sulfur content of the nano-sulfurized polyacrylonitrile positive electrode material obtained in step (2) is greater than 50%.

[0018] The nano-sulfurized polyacrylonitrile positive electrode material prepared by the above preparation method can be used in lithium-sulfur batteries or sodium-sulfur batteries.

[0019] The beneficial effects of the present invention are:

[0020] The present invention finds that a specific type of initiator can control the polymerization degree of acrylonitrile, thereby obtaining nano-scale polyacrylonitrile particles with a particle size of about 100 nm. The nano-polyacrylonitrile particles have an ultra-short ion diffusion distance and the material is easier to vulcanize. The obtained nano-vulcanized polyacrylonitrile has a high degree of vulcanization and a short ion diffusion rate, and has high specific capacity, long cycle life and fast charge and discharge rate performance. BRIEF DESCRIPTION OF THE DRAWINGS

[0021] In order to make the purpose, technical solution and beneficial effects of the present invention clearer, the present invention provides the following drawings for illustration:

[0022] Figure 1 This is the SEM image of the nano-polyacrylonitrile prepared in Example 1.

[0023] Figure 2 This is the SEM image of the nano-polyacrylonitrile particles prepared in Example 1 after vulcanization.

[0024] Figure 3 This is the SEM image of polyacrylonitrile prepared in Comparative Example 2.

[0025] Figure 4 This is the SEM image of the commercial polyacrylonitrile ultrafine powder in Comparative Example 1.

[0026] Figure 5 This is the SEM image of the commercial polyacrylonitrile particles after vulcanization in Comparative Example 1.

[0027] Figure 6 The charge and discharge curves of the sulfurized polyacrylonitrile positive electrode materials prepared in Example 1 and Comparative Example 1 at different current densities.

[0028] Figure 7 The graphs are cycle test graphs of the sulfided polyacrylonitrile positive electrode materials prepared in Example 1 and Comparative Example 1 at current densities of 1C, 2C, 5C, 6C, and 10C.

[0029] Figure 8 This is a comparison chart of the long cycle test of the sulfurized polyacrylonitrile positive electrode material prepared in Example 1 and Comparative Example 1. DETAILED DESCRIPTION

[0030] The preferred embodiments of the present invention will be described in detail below in combination with the embodiments and comparative examples. The described embodiments are only a part of the embodiments of the present invention, rather than all the embodiments, and the scope of the present invention should not be interpreted as being limited to the embodiments described below. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.

[0031] Example 1

[0032] This embodiment provides a method for preparing a nano-sulfurized polyacrylonitrile positive electrode material, comprising the following steps:

[0033] (1) Acrylonitrile and water were uniformly mixed in a volume ratio of 1:10, and then heated in a 95°C water bath, and azobisisobutyronitrile initiator was added at the same time (the amount added was based on the standard of 1 mL acrylonitrile plus 0.1 mg initiator), and then in-situ polymerization was performed for 2 hours to obtain nano-polyacrylonitrile particles;

[0034] (2) The nano-polyacrylonitrile particles obtained in step (1) are uniformly mixed with sulfur in a mass ratio of 1:10, and calcined in a nitrogen atmosphere at a heating rate of 10°C / min, a calcination temperature of 400°C, and a holding time of 12h to obtain a nano-sulfurized polyacrylonitrile positive electrode material.

[0035] Example 2

[0036] This embodiment provides a method for preparing a nano-sulfurized polyacrylonitrile positive electrode material, comprising the following steps:

[0037] (1) Acrylonitrile and water were uniformly mixed in a volume ratio of 1:10, and then heated in a 95°C water bath, and azobisisobutyronitrile initiator was added at the same time (the amount added was based on the standard of 1 mL acrylonitrile plus 0.1 mg initiator), and then in-situ polymerization was performed for 8 hours to obtain nano-polyacrylonitrile particles;

[0038] (2) The nano-polyacrylonitrile particles obtained in step (1) are uniformly mixed with sulfur in a mass ratio of 1:8, and calcined in a nitrogen atmosphere at a heating rate of 10°C / min, a calcination temperature of 500°C, and a holding time of 5h to obtain a nano-sulfurized polyacrylonitrile positive electrode material.

[0039] Comparative Example 1

[0040] Commercial polyacrylonitrile ultrafine powder and sulfur powder were uniformly mixed in a mass ratio of 1:10, and calcined in a nitrogen gas atmosphere at a heating rate of 10°C / min, a calcination temperature of 400°C, and a holding time of 12h to obtain sulfurized polyacrylonitrile particles.

[0041] Comparative Example 2

[0042] This comparative example provides a method for preparing a sulfurized polyacrylonitrile positive electrode material, comprising the following steps:

[0043] (1) Acrylonitrile and water were uniformly mixed in a volume ratio of 1:10, and then heated in a 95°C water bath, and ammonium persulfate initiator was added at the same time (the amount added was based on the standard of 1 mL acrylonitrile plus 0.1 mg initiator), and then in-situ polymerization was performed for 2 hours to obtain polyacrylonitrile particles;

[0044] (2) The polyacrylonitrile particles obtained in step (1) are uniformly mixed with sulfur in a mass ratio of 1:10, and then calcined in a nitrogen atmosphere at a heating rate of 10°C / min, a calcination temperature of 400°C, and a holding time of 12h to obtain a sulfurized polyacrylonitrile positive electrode material.

[0045] Figure 1 This is a SEM image of the nano-polyacrylonitrile particles prepared in Example 1. It can be clearly observed that the particles have uniform morphology and present a spherical nanostructure with a diameter of about 100 nm.

[0046] Figure 2 This is a SEM picture of the nano-polyacrylonitrile particles obtained in Example 1 after vulcanization. It can be clearly observed that the morphology of the material remains uniform after vulcanization, presenting a spherical nanostructure, but the particle diameter increases to about 180 nm.

[0047] Figure 3 This is a SEM image of the polyacrylonitrile particles prepared in Comparative Example 2. It can be clearly observed that the polyacrylonitrile prepared using ammonium persulfate as an initiator is block-shaped and has a relatively large particle size, with a particle diameter generally greater than 20 μm.

[0048] The above experimental data show that compared with the polyacrylonitrile particles prepared by ammonium persulfate initiator, the size of polyacrylonitrile particles prepared by azobisisobutyronitrile initiator can be greatly reduced. The reason is that the activation energy of azobisisobutyronitrile reaction is higher (i.e., the energy required for its transformation from normal state to active state is higher), while the activation energy of ammonium persulfate initiator is lower; under the same suitable concentration conditions, the rate at which azobisisobutyronitrile converts acrylonitrile into polyacrylonitrile is slower, and its kinetic chain length and degree of polymerization are smaller, while ammonium persulfate has a faster conversion rate, a higher kinetic chain length and degree of polymerization, and a larger size of polymerized particles. In addition, the isobutyronitrile free radical formed after the decomposition of azobisisobutyronitrile is a carbon free radical, which lacks dehydrogenation ability and cannot initiate graft polymerization reaction, so that the polymer particle size is maintained at the nanometer level. Correspondingly, azobisisoheptyrile and dimethyl azobisisobutyrate also have similar effects.

[0049] Figure 4 This is the SEM picture of the commercial polyacrylonitrile ultrafine powder in Comparative Example 1. It can be clearly observed that the commercial polyacrylonitrile particles are uneven in size, and the particle size is generally above 20 μm.

[0050] Figure 5 This is the SEM picture of the commercial polyacrylonitrile particles after vulcanization in Comparative Example 1. It can be clearly observed that the powder material has almost no changes in size and morphology before and after vulcanization.

[0051] Commercially vulcanized polyacrylonitrile particles and large blocks of polyacrylonitrile are usually difficult to be fully vulcanized due to their large size. In order to compare and verify the vulcanization effect, we tested the sulfur content of the vulcanized polyacrylonitrile samples prepared in Example 1, Example 2 and Comparative Example 1 and Comparative Example 2, and the data results are shown in the following table:

[0052] sample Example 1 Example 2 Comparative Example 1 Comparative Example 2 Sulfur content (%) 51.33 52.16 21.17 20.33

[0053] Obviously, the sulfur content of the sulfurized polyacrylonitrile of Example 1 and Example 2 is much higher than that of the sulfurized polyacrylonitrile of Comparative Example 1 and Comparative Example 2.

[0054] The sulfided polyacrylonitrile prepared in the above-mentioned embodiment 1 and comparative example 1 is respectively used as the active material of the positive electrode material of the lithium-sulfur battery, the conductive carbon black is used as the conductive agent, and the sodium alginate is used as the binder. The three substances are mixed, pulped, and coated in a mass ratio of 8:1:1 to form an electrode sheet. The lithium metal sheet is used as the negative electrode, lithium hexafluorophosphate is used as the electrolyte, and polypropylene is used as the separator to assemble a lithium-sulfur battery.

[0055] Figure 6 The following are charge and discharge curves of the sulfurized polyacrylonitrile positive electrode materials prepared in Example 1 and Comparative Example 1 at different current densities. According to the test results, the discharge specific capacities of the positive electrode of Example 1 at 1C, 2C, 5C, 6C, and 10C current densities are 597.1, 575.9, 532.9, 522, and 474.6 mAh / g, respectively, while the discharge specific capacities of the positive electrode of Comparative Example 1 at 1C, 2C, 5C, 6C, and 10C current densities are only 238.2, 207.6, 162.8, 122.8, and 60.5 mAh / g, respectively. The above results confirm that the voltage charge and discharge platform of the nano-sulfurized polyacrylonitrile prepared in Example 1 does not change dramatically with the gradual increase in current density, indicating that its rate capability is much higher than that of the commercial sulfurized polyacrylonitrile positive electrode material.

[0056] Figure 7 The graphs are cycle test diagrams of the sulfurized polyacrylonitrile positive electrode materials prepared in Example 1 and Comparative Example 1 at current densities of 1C, 2C, 5C, 6C, and 10C. According to the test results, the nano-sulfurized polyacrylonitrile positive electrode material prepared in Example 1 exhibits excellent cycle stability, which is far superior to the performance of commercial sulfurized polyacrylonitrile positive electrode.

[0057] Figure 8 The long cycle test comparison diagram of the sulphurized polyacrylonitrile positive electrode material prepared in Example 1 and Comparative Example 1. It can be found that the positive electrode material prepared in Example 1 has a more excellent long cycle performance, while the positive electrode prepared in Comparative Example 1 is accompanied by obvious coulomb efficiency fluctuations during the cycle process.

[0058] The above embodiments are only used to illustrate the preferred implementation modes of the present invention, rather than to limit the concept and protection scope of the present invention. Any modifications, equivalent substitutions and improvements made within the concept and principles of the present application shall be included in the protection scope of the present application.

Claims

1. A method for preparing a nano-sulfurized polyacrylonitrile positive electrode material, characterized in that: The following steps are involved: (1) mixing acrylonitrile, an initiator and a solvent and heating them for reaction, wherein the initiator is one or more of azobisisobutyronitrile, azobisisoheptanenitrile and dimethyl azobisisobutyrate, to obtain nano-polyacrylonitrile particles; (2) Mixing the nano-polyacrylonitrile particles obtained in step (1) with sulfur, and calcining the mixture under an inert atmosphere to obtain a nano-sulfurized polyacrylonitrile positive electrode material.

2. The method for preparing the nano-sulfurized polyacrylonitrile positive electrode material according to claim 1, characterized in that: The particle size of the nano-polyacrylonitrile particles obtained in step (1) is 100±20 nm.

3. The method for preparing the nano-sulfurized polyacrylonitrile positive electrode material according to claim 1, characterized in that: In the step (1), the solvent is one or more of dimethyl sulfoxide, dimethylformamide, methanol, ethanol, acetone and water.

4. The method for preparing the nano-sulfurized polyacrylonitrile positive electrode material according to claim 1, characterized in that: In the step (1), the amount of initiator corresponding to 1 mL of acrylonitrile is 0.01 to 100 mg.

5. The method for preparing the nano-sulfurized polyacrylonitrile positive electrode material according to claim 4, characterized in that: In the step (1), the amount of initiator corresponding to 1 mL of acrylonitrile is 0.1 mg.

6. The method for preparing the nano-sulfurized polyacrylonitrile positive electrode material according to claim 1, characterized in that: In the step (1), the reaction temperature is 30 to 100° C. and the reaction time is 1 to 12 hours.

7. The method for preparing the nano-sulfurized polyacrylonitrile positive electrode material according to claim 1, characterized in that: In the step (2), the mixing ratio of the nano-polyacrylonitrile particles to sulfur is 1:1 to 10 by mass.

8. The method for preparing the nano-sulfurized polyacrylonitrile positive electrode material according to claim 1, characterized in that: In the step (2), the heating rate is 2 to 10° C. / min, the calcination temperature is 100 to 500° C., and the calcination time is 1 to 20 hours.

9. The method for preparing the nano-sulfurized polyacrylonitrile positive electrode material according to claim 1, characterized in that: The sulfur content of the nano-sulfurized polyacrylonitrile positive electrode material obtained in step (2) is greater than 50%.

10. Use of the nano-sulfurized polyacrylonitrile positive electrode material prepared by the preparation method according to any one of claims 1 to 9 in lithium-sulfur batteries or sodium-sulfur batteries.